The Sistem Admistrasi Sekolah Berbasis Awan Terpadu di SMAN 16 Samarinda - Evi Susi Sandrawita Br. Saragih; Rujianto Rujianto; Arwiyah Arwiyah; Anggrayani Anggrayani; Ramadiani Ramadiani; Sudarman Sudarman (Manajemen Pendidikan Program Doktor, 2026)
The rapid development of Information and Communication Technology (ICT) has driven a transformation in education management toward more effective, efficient, and integrated systems. This study aims to analyze the implementation of an Integrated Cloud-Based School Administration System at SMAN 16 Samarinda in supporting school digital transformation. A qualitative approach with a case study design was employed, with data collected through interviews, observations, and documentation, and analyzed using the interactive model of Miles and Huberman consisting of data reduction, data display, and conclusion drawing. The findings indicate that the implementation of cloud computing-based school administration successfully integrates academic and non-academic data into a centralized platform, improving administrative efficiency, accelerating information access, and strengthening transparency and accountability in school governance. Moreover, the system supports data-driven decision-making by providing accurate and real-time information for school management, while its success is not only determined by technological infrastructure but also by the digital competence of teachers and administrative staff as a key human factor in technology adoption. The study confirms that cloud-based school administration systems support the principles of good school governance, particularly in enhancing effectiveness, efficiency, transparency, and accountability, and is consistent with the Technology Acceptance Model (TAM), which emphasizes that perceived ease of use and perceived usefulness influence user acceptance of technology, ultimately contributing to the development of modern, integrated, and sustainable school management in the context of digital education transformation.